Unionised dockworkers and port ownership structure in an international oligopoly - Nicola Meccheri (Global Labor Organization (GLO), 2023)
In an international duopoly with two markets and two ports, this paper investigates the role of dockworkers unionisation in affecting welfare outcomes under public and private ports, as well as in determining the endogenous choice by governments of port ownership structure. While private ports maximise profits, public ports maximise domestic welfare and face a budget constraint, which is binding when unions are suf- ficiently wage-oriented and shipping costs are not too high. Consumer surplus, total wage bill and domestic welfare are generally higher under public ownership, especially when unions are wage-oriented. The opposite holds true for firm profits, whilst privati- sation always increases port profits. Moreover, relative to endogenous port ownership structures, state-owned ports appear as the most likely equilibrium result although all possible configurations may arise in equilibrium, including an asymmetric structure with a state-owned port and a private port.
Keywords: F16; J51; L33; R48; 330; unionised dockworkers; port ownership structure; international duopoly; welfare outcomes